The role of governance and international norms in managing natural resources - James Cust (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The governance of natural resource wealth is widely considered to constitute a key determinant in whether the extraction of natural resources proves to be a blessing or a curse. What is meant by governance can span a wide range of components, while the steps to achieving good governance remain subject to debate and uncertainty. In response to this challenge, a variety of international initiatives have emerged seeking to support those striving for better governance in their countries. These initiatives range across efforts to promote transparency, to codify successful historical experiences and effective policies; to help guide decision makers in their choices, and, in some cases, to provide external standards that countries can bind themselves to. These initiatives, such as the Extractives Industry Transparency Initiative, have seen some success in spreading and embedding governance norms, ranging across revenue transparency, contract disclosure, supply chain certification, creation of saving instruments such as resource funds and building institutions for checks and balances such as fiscal rules and accountability bodies. The paper provides a review of initiatives targeting governments as the key agents of change. We find a mixed picture of success, where uptake has been strong, for example in terms of the number of countries engaging with or signing onto normative frameworks. However, evidence for causal impact remains weak and sometimes limited to anecdotal cases. We offer some critical reflections on challenges faced and potential ways forward to build on the lessons and achievements of the past decade and a half.
Keywords: H87 O10; Q30; 330; governance; transparency; natural resources; reforms; international public goods; literature survey